2016
DOI: 10.1016/j.gaceta.2016.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Cost-utility analysis of an integrated care model for multimorbid patients based on a clinical trial

Abstract: The integrated model was not suitable for all study patients. However, the subgroup analysis identified a narrow target population that should be analysed in future studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 16 publications
0
27
1
1
Order By: Relevance
“…Compared to a conventional model, simulation results pointed to a reduction in costs by 89% for the group of patients of less than eighty years and with three or more morbidities (24) . In addition to acting as a connection between the hospital and PHC, the nurse liaison can contribute to other settings, such as discharge from ICU patients to hospital units, as well as the transmission of up-to-date information between nurse in the surgical center and family members (25)(26) , which may improve the articulation between the units of the same health institution, strengthen communication and the bond between professionals and family members.…”
Section: Discussionmentioning
confidence: 88%
“…Compared to a conventional model, simulation results pointed to a reduction in costs by 89% for the group of patients of less than eighty years and with three or more morbidities (24) . In addition to acting as a connection between the hospital and PHC, the nurse liaison can contribute to other settings, such as discharge from ICU patients to hospital units, as well as the transmission of up-to-date information between nurse in the surgical center and family members (25)(26) , which may improve the articulation between the units of the same health institution, strengthen communication and the bond between professionals and family members.…”
Section: Discussionmentioning
confidence: 88%
“…The most common types of economic evaluations were cost-utility analysis [31323334353637383940414243444546474849], followed by cost-consequence [5051525354555657585960616263], cost-effectiveness [64656667] and cost-comparison analysis [6869707172]. For more information on the different types of economic evaluations, please see Drummond et al [19].…”
Section: Resultsmentioning
confidence: 99%
“…However, evidence has shown that case management programs are not cost-effective in comparison to nonintegrated care programs for high-risk patients [7,8,14]. Case management interventions are not suitable for all high-risk patients but for a subset of patients who would benefit from them [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence has shown that case management programs are not cost-effective in comparison to nonintegrated care programs for high-risk patients [ 7 , 8 , 14 ]. Case management interventions are not suitable for all high-risk patients but for a subset of patients who would benefit from them [ 14 ]. In other words, the population they target is heterogeneous and has different needs [ 10 , 15 – 17 ], yet all patients are treated in a uniform manner under the same case management strategy.…”
Section: Introductionmentioning
confidence: 99%